Local Stability of Double-Coped Beams - Dowswell, Bo; Whyte, Robert (Engineering Journal, 2014)
Localized web buckling can limit the strength of coped beams. In this paper, the coped portion of the beam is treated as an isolated rectangular member, and a parametric study is used to develop lateral-torsional buckling modification factors for use with 2010 AISC Specification Section F11. The parametric study included finite element models with different cope lengths at the top and bottom flanges and cope depths up to 40% of the beam depth. Compared with the finite element results in this paper, the proposed design procedure is more accurate than the design procedure in the 14th Edition Steel Construction Manual.